If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(w + -8) = 3w + -45 Reorder the terms: 6(-8 + w) = 3w + -45 (-8 * 6 + w * 6) = 3w + -45 (-48 + 6w) = 3w + -45 Reorder the terms: -48 + 6w = -45 + 3w Solving -48 + 6w = -45 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -48 + 6w + -3w = -45 + 3w + -3w Combine like terms: 6w + -3w = 3w -48 + 3w = -45 + 3w + -3w Combine like terms: 3w + -3w = 0 -48 + 3w = -45 + 0 -48 + 3w = -45 Add '48' to each side of the equation. -48 + 48 + 3w = -45 + 48 Combine like terms: -48 + 48 = 0 0 + 3w = -45 + 48 3w = -45 + 48 Combine like terms: -45 + 48 = 3 3w = 3 Divide each side by '3'. w = 1 Simplifying w = 1
| -12=7x+9 | | h(15)=4.5+9.7 | | (24/2+6)+(7*7+100-52) | | 3x-8=-9-9x | | y=(1/x+3)+3 | | 6(6n-1)=7(4n-2) | | x-3/4=-7/12 | | -7=5(w+4)-8w | | 7/15+9/20 | | 5/9+7/30 | | 2x+1.1=4.3 | | 7/x+12/x^2=-1 | | -8(0.1x+0.4)-1.8=-0.2 | | f(5)=37 | | 14-4x=-7x+17 | | 3/10+7/16 | | 2r-9=-5 | | X+x+7=147 | | 2(x)+2(3/4)x=50 | | 3n=2n+6 | | 1/3(5x-2)=4 | | 2(L)+2(3/4)L=50 | | 2n=3n+6 | | .02X+.07Y=36.35 | | 2n+3n=6 | | 3x+y-42=0 | | -2x-2x=30-2 | | t/5+7=-4 | | c/8-5=-8 | | 4m+24=-12 | | (2x+7)(5x^2-27+10)=0 | | 7(2a-b)-7(2b-8a)= |